Role of Curcumin in Protection of Chemobrain via Suppression of Oxidative Stress and Inflammatory Mediators in Swiss Mice - Ashutosh Kumare Yadav; Dr. Harinath Dwivedi; Dr. Dharamveer (The Bioscan, 2025)
Background: Cyclophosphamide (CP) is a cancer chemotherapeutic agent which shows a cognitive impairment i.e. termed as chemobrain or chemofog. Cyclophosphamide induced cognitive impairement (CICI) is mainly due to generation of reactive oxygen species (ROS) at the cellular level. Curcumin is a natural compound present in the Indian diet as turmeric. Traditionally it is used as analgesic and anti-inflammatory agent. Various pharmacological activities are proven such as antioxidant, anti-cancer and antiapoptotic properties. Objective: In the present study, the neuroprotective effect of curcumin against cyclophosphamide induced cognitive impairment was evaluated on neurobehavioral, neuropathological and biochemical alteration in the adult Swiss mice. Additionally the inflammatory mediators as well as neurotransmitter level were estimated. Methods: Animals were equally divided into five groups of 5 rats in each. Cyclophosphamide were injected intraperitoneally to the animals at dose of 50 mg/kg/week i.p. for 7 days and curcumin at a dose of 200 and 400 mg/kg for 21 days. After 21 days, cognitive dysfunction and motor coordination was assessed behaviorally based on pharmacological models such as passive avoidance test and Rota rod test. After behavioral assessment all the animals were sacrificed for anti-oxidant assay and histopathological studies. Inflammatory mediator Il-6 and neurotransmitter dopamine level were also evaluated in brain homogenate. Results: Data showed that CP significantly elevated brain AChE activity in the brain. A decrease in the total antioxidant capacity and a reduction in the CAT, SOD, and GSH activity occurred in the brains of the rats exposed to CP. CP treated rats showed a significant impairment in long-term- memory and motor coordination. These results were supported by histopathological observations of the brain. Results revealed that the administration of curcumin ameliorated behavioral and histopathological changes induced by CP. Inflammatory mediators were also reduced along with the restoration of dopamine level in the animals treated with curcumin. Conclusion: This study suggests that co-administration of curcumin with cyclophosphamide may be a useful adjunct therapeutic approach to overcome cyclophosphamide induced cognitive impairment.